Production and characterization of new fibrinolytic protease from Mucor subtillissimus UCP 1262 in solid-state fermentation - Nascimento, Thiago Pajeú (2015)
Fibrinolytic enzymes have received attention regarding their medicinal potential for thrombolytic diseases, a leading cause of morbidity and mortality worldwide. Various natural enzymes purified from animal, plant and microbial sources have been extensively studied. The aim of this work was to produce fibrinolytic protease by solid state fermentation using agro industrial substrates. Rhizopus arrhizus var. arrhizus UCP 1295 and Mucor subtillissimus UCP 1262 filamentous fungi species isolated from soil of Caatinga-PE, Brasil, were used as producer microorganisms. Wheat bran was shown to be the best substrate for the production of the enzyme and by using a 23 full factorial design the main effects and interactions of the quantity of the substrate wheat bran, moisture and temperature on the fibrinolytic enzyme production and protease were evaluated. The best results for fibrinolytic and protease activities, 144.58 U/mL and 48.33 U/mL, respectively, were obtained with Mucor subtillissimus UCP 1262 using as culture medium 3 g wheat bran, 50% moisture at a temperature of 25˚C for 72 hours. The optimum temperature for the produced enzyme was 45˚C and most of its original activity was retained after being subjected to 80˚C for 120 min. The protease activity was enhanced by K+, Ca+ and Mn+; but with Cu+ there was an inhibition. The specificity to chromogenic substrate and the inhibition by PMSF indicates that it is a chymotrypsin-like serine protease. Presented results suggest that this enzyme produced by solid-state fermentation is an interesting alternative as a candidate for thrombolytic therapy.